A critical analysis of Islamic studies curriculum at the University of Syiah Kuala, Darussalam Banda Aceh, Indonesia - Ridhwan M. Daud (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1999)
The mainpurpose of the study is to analyse how far the philosophy, aims and the contents of Islamic religious studies curriculum at the University of the Syiah Kuala, Darussalam, Banda Aceh, Indonesia differ from the recommendations of the World Conferences on Muslim Education, other Muslim educational scholars' thoughts and the national curricular specification of the Ministry of Religious Affairs of Indonesia. The results of the study show that the educational philosophy of the Syiah Kuala University is based on the national ideology of lndonesia, the Pancasila (Five pillars) which is enshrind in the Basic Constitution of 1945 of Indonesia and aims to realise the National Motto "Unity in Diversity". In general, the ultimate aims of teaching the course are akin to the recommendation of the First World Conference on Muslim Education that was held in Makkah in 1977. Nevertheless, some shortcomings are there, mostly because these aims are also defined in accordance with and to reflect the National Education Philosophy which purports to produce good lndonesian citizens. Though the curriculum is suitable for national policy requirements, its time allocation and contents provided for the courses seem inadequate and superficial. The important subject of Arabic that should have been included m Islamic religious studies, is totally absent from the curriculum of Islamic religious studies of the University. The study recommends that the Syiah Kuala University has to eliminate the inconsistency between theoretical and practical aspects from its educational system and adopt ways and means of bringing its curriculum on Islamic religious studies more in line with the recommendation of the First World Conference on Muslim Education. It also recommends the University to benefit from a study of the curriculum of some other Islamic Universities such as the International Islamic University Malaysia, the Umm al-Qura in Makkah and Imam Muhammad bin Sa'ud University at Riyadh.